Analysis of Treatment Modalities for Advanced Stage Squamous Cell Carcinoma of the Maxillary Sinus: A National Cancer Database Study - Lee, Kue T.; Kleinbub, Duncan; Gelves, Camilo R. (Journal of Neurological Surgery Part B: Skull Base, 2023)
Introduction Stage cT4a and cT4b squamous cell carcinomas (SCCa) typically require multimodal treatment with adjuvant or neoadjuvant therapy. This study aims to evaluate the impact of different treatment modalities on survival outcomes in patients with stage cT4a-b SCCa exclusively of the maxillary sinus.Methods A multivariate survival analysis was conducted, evaluating treatment modalities for patients diagnosed between 2004 and 2020 utilizing the National Cancer Database. Cox hazard regression was performed for variables.Results The study identified a total of 1,788 patients with SCCa of the maxillary sinuses, of which 71.2% were cT4a. Increasing age, Charlson–Deyo score ≥ 1, and undifferentiated/anaplastic grade were associated with worse rates of survival. Multivariate analysis revealed that neoadjuvant treatment exhibited the lowest hazard ratio ([HR]: 0.574, 95% confidence interval [CI]: 0.370–0.892) across the entire cohort (cT4a-b). Neoadjuvant treatment plus surgery, adjuvant treatment plus surgery, and surgery alone demonstrated the highest adjusted 5-year survival for cT4a-b tumors. On the other hand, radiation alone exhibited the highest HR (1.939, 95% CI: 1.555–2.418) in multivariate analysis and the lowest adjusted 5-year survival.Conclusion Multimodal treatment of advanced stage maxillary SCCa has a variable effect on outcomes by tumor stage. Our findings suggest that surgery plus neoadjuvant and surgery plus adjuvant treatment are associated with higher rates of survival. Increasing age, Charlson–Deyo score ≥ 1, and undifferentiated/anaplastic grade were associated with worse rates of survival. Further randomized controlled trials are required to quantify the therapeutic benefit of these treatments on survival and organ sparing in advanced stage disease.
Keywords: rhinology; maxillary squamous cell carcinoma; oncology; maxillary sinus